B7-H3-targeting Fc-optimized antibody for induction of NK cell reactivity against sarcoma - Hagelstein, Ilona; Engel, Monika; Hinterleitner, Clemens; Manz, Timo; Märklin, Melanie; Jung, Gundram; Salih, Helmut R.; Zekri, Latifa (Frontiers in Immunology, 2022)
Natural killer (NK) cells largely contribute to antibody-dependent cellular cytotoxicity (ADCC), a central factor for success of monoclonal antibodies (mAbs) treatment of cancer. The B7 family member B7-H3 (CD276) recently receives intense interest as a novel promising target antigen for immunotherapy. B7-H3 is highly expressed in many tumor entities, whereas expression on healthy tissues is rather limited. We here studied expression of B7-H3 in sarcoma, and found substantial levels to be expressed in various bone and soft-tissue sarcoma subtypes. To date, only few immunotherapeutic options for treatment of sarcomas that are limited to a minority of patients are available. We here used a B7-H3 mAb to generate chimeric mAbs containing either a wildtype Fc-part (8H8_WT) or a variant Fc part with amino-acid substitutions (S239D/I332E) to increase affinity for CD16 expressing NK cells (8H8_SDIE). In comparative studies we found that 8H8_SDIE triggers profound NK cell functions such as activation, degranulation, secretion of IFNγ and release of NK effector molecules, resulting in potent lysis of different sarcoma cells and primary sarcoma cells derived from patients. Our findings emphasize the potential of 8H8_SDIE as novel compound for treatment of sarcomas, particularly since B7-H3 is expressed in bone and soft-tissue sarcoma independent of their subtype.